2016
DOI: 10.1073/pnas.1611333113
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the cohesin loader Scc2 and insight into cohesinopathy

Abstract: The ring-shaped cohesin complex topologically entraps chromosomes and regulates chromosome segregation, transcription, and DNA repair. The cohesin core consists of the structural maintenance of chromosomes 1 and 3 (Smc1-Smc3) heterodimeric ATPase, the kleisin subunit sister chromatid cohesion 1 (Scc1) that links the two ATPase heads, and the Scc1-bound adaptor protein Scc3. The sister chromatid cohesion 2 and 4 (Scc2-Scc4) complex loads cohesin onto chromosomes. Mutations of cohesin and its regulators, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
129
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(136 citation statements)
references
References 63 publications
7
129
0
Order By: Relevance
“…First, NIPBL/Scc2 — the cohesin DNA loader — is confidently included in the Hawk cluster. This conclusion is now strongly supported by the recent biochemical studies of the Chaetomium thermophilum yeast Scc2, which is found to bind robustly to C. thermophilum Scc1 [5]. Second, our analysis fails to support the previous proposal that Nse5 and Nse6 associated with the eukaryotic Smc5-6 holocomplex contain HEAT repeats.…”
Section: Main Textsupporting
(Expert classified)
“…First, NIPBL/Scc2 — the cohesin DNA loader — is confidently included in the Hawk cluster. This conclusion is now strongly supported by the recent biochemical studies of the Chaetomium thermophilum yeast Scc2, which is found to bind robustly to C. thermophilum Scc1 [5]. Second, our analysis fails to support the previous proposal that Nse5 and Nse6 associated with the eukaryotic Smc5-6 holocomplex contain HEAT repeats.…”
Section: Main Textsupporting
(Expert classified)
“…4). In the Kikuchi et al 37. study, no interaction is detected between Scc2 and Smc1–Smc3 dimer or between Scc2 and Scc3 using in vitro translation-generated proteins.…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, interactions are also seen between different Scc2–Scc4 modules and the DNA-entry/exit gate formed by Scc1 and Smc3 (refs 12, 32), suggesting that the loader might play a role in DNA gate opening. Since Pds5 also binds to Scc1 and Smc3 close to DNA-entry/exit gate12282938, this could explain how Pds5 inhibits in-vitro loading of cohesin by Scc2–Scc4 through competitive binding to the same site on cohesin937.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that Wapl initially destabilizes the Smc3-Scc1 interaction and Pds5 then keeps the DNA transport gate open. Crystallographic and bioinformatic studies have shown that Pds5 and Scc2, as well as Scc3, are paralogs and share similar U-shaped structures that are composed of stacked HEAT repeat helices [2729,40]. Both Pds5 and Scc2 interact with the flexible middle domain of Scc1.…”
Section: Topological Dna Binding By Cohesinmentioning
confidence: 99%
“…Both Pds5 and Scc2 interact with the flexible middle domain of Scc1. Although their interaction motifs on Scc1 are different, these sites are located in close proximity to each other [27,41]. Interestingly, purified Pds5 competes with Mis4 Scc2 -Ssl3 Scc4 for cohesin binding, suggesting that Scc2 and Pds5 bind to Scc1 in a mutually exclusive manner [37].…”
Section: Topological Dna Binding By Cohesinmentioning
confidence: 99%